Validation of a field test to determine the maximal aerobic power in triathletes and endurance cyclists - Gonzalez-Haro, C.; Galilea, P. A.; Drobnic, F.; Escanero, J. F. (British Journal of Sports Medicine, 2007)
Objective: To validate a field test to assess the maximal and submaximal exercise aerobic adaptation under specific conditions, for endurance modality cyclists and triathletes.